Tuberculosis 2019
DOI: 10.1183/13993003.congress-2019.oa3821
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of severe Mycobacterium avium complex pulmonary disease with a adjunctive amikacin and clofazimine versus standard regimen alone, a retrospective study

Abstract: Mycobacterium avium complex (MAC) bacteria, i.e. Mycobacterium avium, Mycobacterium intracellulare, Mycobacterium chimaera and related species, can cause severe pulmonary disease (MAC-PD), especially in patients with chronic pulmonary diseases, like COPD and bronchiectasis [1, 2].Treatment of MAC-PD is difficult due to its long duration, frequent adverse events and comorbidities of the host. Reported cure rates vary by disease manifestation, with poorest cure rates in fibrocavitary disease [3]. The currently r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The most frequent and likely amikacinrelated adverse events reported were hearing loss (mean 7%, range 0-37%), tinnitus (mean: 6%, range 0-42%) and nephrotoxicity (mean: 2%, range 0-7%). The lowest rates of toxicity were recorded in a study that mostly applied thrice weekly dosing of amikacin [100]; studies using daily doses of 15 mg/ kg reported the highest frequencies of adverse events [78,83].…”
Section: Toxicity Of Amikacin In Ntm Disease Cohortsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequent and likely amikacinrelated adverse events reported were hearing loss (mean 7%, range 0-37%), tinnitus (mean: 6%, range 0-42%) and nephrotoxicity (mean: 2%, range 0-7%). The lowest rates of toxicity were recorded in a study that mostly applied thrice weekly dosing of amikacin [100]; studies using daily doses of 15 mg/ kg reported the highest frequencies of adverse events [78,83].…”
Section: Toxicity Of Amikacin In Ntm Disease Cohortsmentioning
confidence: 99%
“…There are no direct comparisons of streptomycin versus amikacin. The clinical efficacy of amikacin has been shown only in one small retrospective study comparing rifampicin-ethambutol-macrolide regimens with similar regimens to which amikacin and clofazimine were added, showing similar outcomes (80% cure rate with 3 drugs, 90% with 5 drugs) despite more severe disease in the 5-drug cohort [83]. The clinical efficacy of amikacin was mainly studied in non-comparative studies in the context of macrolide-resistant MAC-PD [84,85].…”
Section: Mac-pd Intravenous Amikacinmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study presented at ERS 2019 explored the combination of amikacin and clofazimine on MAC infection [ 49 ]. In this study, patients were treated with either rifampicin/ethambutol/macrolide (n=25) or rifampicin/ethambutol/macrolide plus amikacin/clofazimine (n=19).…”
Section: Treatment Options On the Horizonmentioning
confidence: 99%